Independent and Combined Effects of Physical Activity and Sedentary Behavior on Blood Pressure in Adolescents: Gender Differences in Two Cross-Sectional Studies - de Moraes, Augusto César Ferreira [UNESP]; Carvalho, Heráclito Barbosa; Rey-López, Juan Pablo; Gracia-Marco, Luis; Beghin, Laurent; Kafatos, Anthony; Jiménez-Pavón, David; Molnar, Dénes; De Henauw, Stefaan; Manios, Yannis; Widhalm, Kurt; Ruiz, Jonatan R.; et al. (Public Library of Science (PLoS), 2013)
Objectives: To examine the independent and combined association of physical activity (PA) and sedentary behavior (SB) on both systolic (SBP) and diastolic blood pressure (DBP) in adolescents from two observational studies. Methods: Participants from two cross-sectional studies, one conducted in Europe (n = 3,308; HELENA study) and the other in Brazil (n = 991; BRACAH study), were selected by complex sampling. Systolic and diastolic blood pressure (outcomes), PA and SB, both independently and combined, and potential confounders were analyzed. Associations were examined by multilevel linear regression. Results: Performing the recommended amount of PA (≥60 min/d) attenuated the effect of SB on DBP in BRACAH study girls and in boys from both studies. In contrast, PA did not attenuate the effects of SB on the SBP of girls in the HELENA study. The combination of less than recommended levels of PA with 2-4 h/d of sedentary behavior was found to be associated with increased SBP in boys from both studies. Conclusions: Meeting current PA recommendations could mediate the association between SB and DBP in both sexes. In boys, the joint effect of low levels of PA and excessive sedentary activity increases SBP levels. Longitudinal studies are required to confirm these findings. © 2013 de Moraes et al.
Keywords: adolescent; adolescent health; blood pressure measurement; correlational study; cross-sectional study; diastolic blood pressure; disease association; female; human; hypertension; major clinical study; male; multiple linear regression analysis; observational study; physical activity; population research; sedentary lifestyle; sex difference; systolic blood pressure